1987
DOI: 10.1017/s0033583500004170
|View full text |Cite
|
Sign up to set email alerts
|

Energy profiles in the gramicidin A channel

Abstract: Gramicidin A (GA) is a linear pentadecapeptide made of alternating D and L residues, in which the N-and C-terminals are blocked by a formyl group (head) and an ethanolamine end (tail), respectively (Sarges & Witkop, 1964):

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…The planar lipid bilayer membrane as developed by Mueller et al (2) has proven to be remarkably useful as a model ofthe cell membrane. It was discovered that small ions cross these membranes by two mechanisms: ion channels that can be gated by voltage or receptors (3,4) and ion carriers that are not gated (5). We now show that the latter ionic currents, exemplified by currents of large hydrophobic ions, can be gated by photoinduced charge generation inside the membrane.…”
mentioning
confidence: 68%
“…The planar lipid bilayer membrane as developed by Mueller et al (2) has proven to be remarkably useful as a model ofthe cell membrane. It was discovered that small ions cross these membranes by two mechanisms: ion channels that can be gated by voltage or receptors (3,4) and ion carriers that are not gated (5). We now show that the latter ionic currents, exemplified by currents of large hydrophobic ions, can be gated by photoinduced charge generation inside the membrane.…”
mentioning
confidence: 68%
“…Previous reviews have addressed the experimentally observed permeability properties of gramicidin channels (1,10,48,54), the analysi s of peptide backbone structures (141,177), the use of NMR to estimate ion associati on and dissociation rates (169), the effect of gramicidin on lipids (40, 44), and progress on modeling the energetics of cation transport (80,81,118). Some of these topics are revisited with emphasis on subsequent work and new interpretations of older results.…”
Section: Introductionmentioning
confidence: 99%
“…This article reviews the determination of the molecular structure (second ary, tertiary, and quarternary) starting from the point where only the primary sequence was known. We first discuss the basis for early modeling as a {3 structure, the physical methods used to test the models, and the advantages and limitations of these older methods, and then review the most recent progress on structure and function.Previous reviews have addressed the experimentally observed permeability properties of gramicidin channels (1, 10, 48, 54), the analysi s of peptide backbone structures (141,177), the use of NMR to estimate ion associati on and dissociation rates (169), the effect of gramicidin on lipids (40, 44), and progress on modeling the energetics of cation transport (80, 81,118). Some of these topics are revisited with emphasis on subsequent work and new interpretations of older results.…”
mentioning
confidence: 99%
“…The number and the structuring of the water molecules in the channel in the absence of the ion are those determined previously and described in details in (6).The geometry adopted for the channel is, as in our previous papers (1)(2)(3)(4)(5)(6)(7)(8)(9), that of the head-to-head dimer proposed by Urry, each monomer being constructed with standard bond lengths and angles and with the phi, psi dihedral angles given in ref 16. The conformations of the side chains are those given as the most stable ones in (17).…”
Section: Methodsmentioning
confidence: 99%
“…In the previous papers (1)(2)(3)(4)(5)(6)(7)(8)(9) we have undertaken the study of the problem of ion transport in the Gramicidin A channel (GA) from a theoretical point of view by the computation of the "energy profile" felt by various cations progressing along the channel. We have focused our attention extensively on the case ofN a+ for which we have examined in detail the influence of the structural components of the channel and of the water molecules present at the mouth and in the channel on this profile.…”
Section: Introductionmentioning
confidence: 99%